Enhancing the Quality of Morbidity and Mortality Rounds: The Ottawa M&M Model. (March 2014) - Calder, Lisa A.; Kwok, Edmund S.H.; Adam Cwinn, A.; Worthington, James; Yelle, Jean‐Denis; Waggott, Melissa; Frank, Jason R.; Yarris, Lalena
Abstract Objectives The objective of this study was to determine the feasibility and acceptability of a structured morbidity and mortality (M&M) rounds model through an innovative educational intervention. Methods The authors engaged the Departments of Emergency Medicine (EM) and Trauma Services at a tertiary care teaching hospital. A needs assessment was performed; the Ottawa M&M rounds model was developed, implemented, and then evaluated as a four‐part intervention. This consisted of: 1) physician training on case selection and analysis, 2) engaging interprofessional members, 3) disseminating lessons learned, and 4) creating an administrative pathway for acting on issues identified through the M&M rounds. The measures of intervention feasibility included the proportion of sessions adherent to the new model and M&M rounds attendance. Pre‐ and postintervention surveys of presenters and attendees were used to determine intervention acceptability. M&M presentation content was reviewed to determine the most frequently adopted components of the model. Results Nine of 14 (64.3%) sessions were adherent to three of four components of the Ottawa M&M Model. Of those M&M attendees who responded to the survey (796 of 912, 87.2%), improvements were found in M&M rounds attendance as well as perceived effect on clinical practice at both individual and departmental levels. Thirty‐seven case presentations were analyzed and improvements postintervention were found in appropriate case selection and recognition of cognitive and system issues. Conclusions The Ottawa M&M Model was a feasible intervention that was perceived to be effective by both presenters and attendees. The authors believe that this could be readily applied to any hospital department seeking to enhance quality of care and patient safety.